Investigation of Yersinia ruckeri Infection in Rainbow Trout (Oncorhynchus mykiss Walbaum 1792) Farms by Polymerase Chain Reaction (PCR) and Bacteriological Culture - Seker, Engin; Karahan, Murat; Ispir, Unal; Cetinkaya, Burhan; Saglam, Naim; Sarieyyupoglu, Mustafa (Kafkas Univ, Veteriner Fakultesi Dergisi, 2012)
This study has been carried out to investigate the presence of Yersinia ruckeri, the causative agent of Enteric Red Mouth (ERM) disease, in rainbow trout fish breeding farms located in Elazig and Malatya provinces in Eastern Turkey. For this purpose, bacteriological culture and a specific polymerase chain reaction (PCR) have been compare with examine blood and intestine samples collected from adult and young rainbow trout fish as well as water samples collected from all the farms. Y. ruckeri was isolated and identified from eight of the 17 fish farms giving a proportion of 52.9% at fish farm. The disease was noted in five of the rainbow trout farms located in Elazig and three of the 11 rainbow trout farms located in Malatya. The agent was detected in five of the six young fish breeding farms. The isolation percentages of the causative agent at fish level were calculated as 25.7% (131/510) in adult and 31.7% (19/60) in young fish, giving an overall proportion of 26.3% (150/570). All the isolates have been successfully identified as Y ruckeri by species-specific PCR. No isolation could be made from water samples. It is therefore concluded that Y. ruckeri infection poses a significant threat to the fish farms in the study area and necessary precautions should urgently be taken in order to minimize economical losses due to ERM disease. A specific PCR can be utilized successfully in aquaculture for rapid identification of bacterial agents which will help to prevent spread of infectious diseases and will therefore contribute to the productivity of fishery sector.
Keywords: Rainbow trout; Yersinia ruckeri; Culture; PCR